AIAA Guidance, Navigation, and Control Conference and Exhibit 2003
DOI: 10.2514/6.2003-5364
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark Problems for Spacecraft Formation Flying Missions

Abstract: To provide high-level focus to distributed space system flight dynamics and control research, several Ijenchmark problems are suggested. These problems are not specific to any current or proposed mission, but instead are intended to capture high-level features that would be generic to many similar missions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 2 publications
0
60
0
Order By: Relevance
“…The solution of the TPBVP can be preferred for the formation of the tetrahedron constellation at the apogee point, but there are some other considerations related to the solution of this problem. For these reasons, the correction of the separation distance constraints for the proposed tetrahedron constellation [Carpenter et al 2003] will be based on the DLQR control scheme [Capó-Lugo and Bainum 2006a]. With this DLQR control scheme, the tetrahedron constellation can be formed with the required separation distance at the following apogee point.…”
Section: Transfer From a Circular Orbit To The Elliptical Orbit (Stagmentioning
confidence: 99%
See 4 more Smart Citations
“…The solution of the TPBVP can be preferred for the formation of the tetrahedron constellation at the apogee point, but there are some other considerations related to the solution of this problem. For these reasons, the correction of the separation distance constraints for the proposed tetrahedron constellation [Carpenter et al 2003] will be based on the DLQR control scheme [Capó-Lugo and Bainum 2006a]. With this DLQR control scheme, the tetrahedron constellation can be formed with the required separation distance at the following apogee point.…”
Section: Transfer From a Circular Orbit To The Elliptical Orbit (Stagmentioning
confidence: 99%
“…Equation (12) will not require a transformation with (6c) because ψ(k) is defined in terms of the mean orbital elements of the satellites in the proposed constellation [Carpenter et al 2003], as shown in Table 2. In [Capó-Lugo and Bainum 2006a], the solution of the DLQR problem is obtained but is rewritten here for the y j system as…”
Section: Station-keeping Procedures (Stage 2)mentioning
confidence: 99%
See 3 more Smart Citations